Combining ability studies in sunflower (Helianthus annuus L.): COMBINING ABILITY STUDIES IN SUNFLOWER (HELIANTHUS ANNUUS L.) - N VAIRAM,; R P GNANAMALAR, (Journal of Oilseeds Research, 2016)
Combining ability studies were made in sunflower using line x tester analysis with three CMS lines and ten testers. Ten important yield traits viz., days to 50% flowering, number of leaves/plant, plant height, stem girth, head diameter, number ofseeds/head, autogamy per cent, 100-seed weight, seed yield/plant and oil content were studied. Non-additive gene action was predominant for all the traits. Based on general combining ability of parents, the line 234 A was found to be good general combiner for days to 50% flowering, stem girth, head diameter, number of seeds/head, 100-seed weight, seed yield/plant and oil content. Three testers viz., RHA 83R6, RHA 17 and DRSF 110 R exhibited higher gca effects for most of the yield traits and these parents can be considered as good general combiners. The hybrid NDCMS 1A x RHA 6D-5-3-6 possessed superior sca effects for six traits viz., days to 50% flowering, head diameter, number of seeds/head, autogamy per cent, 100-seed weight and seed yield/plant. Three hybrids viz., 234 A x DRSF 111 R, NDCMS 1A x RHA 83R6 and 234 A x RHA 859-2 can be considered as good specific combiners for exploitation of yield and its components. Hybrid 234 A x RHA RR 2 was the best for stem girth, head diameter, 100-seed weight and seed yield/plant. These above mentioned hybrids can be considered as good specific combiners.